Structure and Density Heterogeneities of the l-3Al2O3.2SiO2 System: Insight from Computer Simulation and Density-Based Spatial Clustering of Applications with Noise - Tri Dung, Pham; Thi Lan, Mai; Van Hong, Nguyen (VNU Journal of Science: Mathematics - Physics; Vol 41 No 1DO - 10.25073/2588-1124/vnumap.4967, 2025)
The structural and density heterogeneity of the liquid 3Al 2 O 3 .2SiO 2 (l-3Al 2 O 3 .2SiO 2 ) system was studied using Molecular Dynamics (MD) and Monte Carlo (MC) simulations. The results showed that the structural phase transition occurred at an oxygen packing factor of approximately 0.58. At low pressure, TO 4 structural units predominated while at high pressure, TO 6 structural units became dominant. In addition, the Density-Based Spatial Clustering of Applications with Noise (DBSCAN) algorithm was applied to find regions with larger density than the average density in the model. These findings provide an in-depth understanding of the structure of the l-3Al 2 O 3 .2SiO 2 system under compressive pressure. Keywords: Structural heterogeneity, OPF, high-density regions, DBSCAN.